2012
DOI: 10.1021/ol303168y
|View full text |Cite
|
Sign up to set email alerts
|

Kadcoccitones A and B, Two New 6/6/5/5-Fused Tetracyclic Triterpenoids from Kadsura coccinea

Abstract: A pair of new triterpenoid epimers, kadcoccitones A (1) and B (2), together with a new biogenetically related compound kadcoccitone C (3), were isolated from Kadsura coccinea. The epimers featured an unprecedented carbon skeleton with a 6/6/5/5-fused tetracyclic ring system unit and a C(9) side chain. Their structures were determined by spectroscopic data, ECD calculation, and single-crystal X-ray diffraction. Compounds 1 and 3 showed anti-HIV-1 activity with an EC(50) value of 47.91 and 32.66 μg/mL, respectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 22 publications
0
27
0
Order By: Relevance
“…The roots of K. coccinea have been an ethnomedicine used for the treatment of cancer, dermatosis, gastroenteric disorders, rheumatoid arthritis and relieving pain (Hu et al, 1999). Previous phytochemical investigations on K. coccinea revealed the main presence of lignans (Hu et al, 2012;Gao et al, 2012;Li et al, 2006Li et al, , 2007 and triterpenoids (Gao et al, 2008a;Li et al, 2008;Liang et al, 2012;Song et al, 2010;Wang et al, 2008Wang et al, , 2012 in this plant, which showed the antiproliferative , anti-hepatitis (Ban et al, 2009) and NO inhibitory activities (Li et al, 2007(Li et al, , 2006. In our continuous survey on the chemical composition of Chinese folk medicines and medicinal plants (Xu et al, 2012;Wang et al, 2013), three new lignans, 14-O-demethyl polysperlignan D (1), kadsurindutin E (16), coccilignan A (17), and fifteen known lignan compounds (2-15 and 18) (Fig.…”
Section: Introductionmentioning
confidence: 96%
“…The roots of K. coccinea have been an ethnomedicine used for the treatment of cancer, dermatosis, gastroenteric disorders, rheumatoid arthritis and relieving pain (Hu et al, 1999). Previous phytochemical investigations on K. coccinea revealed the main presence of lignans (Hu et al, 2012;Gao et al, 2012;Li et al, 2006Li et al, , 2007 and triterpenoids (Gao et al, 2008a;Li et al, 2008;Liang et al, 2012;Song et al, 2010;Wang et al, 2008Wang et al, , 2012 in this plant, which showed the antiproliferative , anti-hepatitis (Ban et al, 2009) and NO inhibitory activities (Li et al, 2007(Li et al, , 2006. In our continuous survey on the chemical composition of Chinese folk medicines and medicinal plants (Xu et al, 2012;Wang et al, 2013), three new lignans, 14-O-demethyl polysperlignan D (1), kadsurindutin E (16), coccilignan A (17), and fifteen known lignan compounds (2-15 and 18) (Fig.…”
Section: Introductionmentioning
confidence: 96%
“…These epimers featured an unprecedented carbon skeleton with a 6/6/5/5‐fused tetracyclic ring system unit and a C‐9 side chain. Compounds 290 and 292 showed anti‐HIV‐1 activity with EC 50 values of 47.9 and 32.7 μg/ml, respectively 118 …”
Section: Tetracyclic Triterpenoidmentioning
confidence: 99%
“…Phytochemical investigations on the stems of K. coccinea collected from Guangxi and Yunnan Provinces have previously been undertaken by our research group, which revealed this species to be abundant with triterpenoids, especially lanostane triterpenoids [ 4 9 ]. Up to now, six kinds of unprecedented lanostane-type triterpenoid scaffolds have been isolated from the stems of K. coccinea by our group [ 4 7 ], namely, 14(13 → 12):13(17 → 16)-diabeolanostanes, 18(13 → 12)-abeo-13,17-secolanostanes, 14(13 → 12)-abeo-13,18-dinorlanostanes, 14(13 → 12)-abeo-12,13-secolanostanes, 14(13 → 12)-abeo-2,3-secolanostanes, and 13,14-secolanostanes. Besides, plenty of new triterpenoids belonging to conventional lanostanes [ 4 9 ], cycloartanes [ 10 , 11 ] and schinortriterpenoids [ 10 ] have also been isolated from the stems of this species.…”
Section: Introductionmentioning
confidence: 99%